Comparison of the main factors affecting real estate prices in higher- versus lower-income cities in Eastern China - Li, HaoRan; Burlakov, Georgi; Krejčová, Nikola, 1974-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
Abstract： This article examines the influencing factors of real estate prices in different regions of East China and distinguishes high-income and low-income regions based on per capita GDP. The first section outlines the introduction of the paper. The following is a theoretical analysis of the factors that affect real estate prices. The third part discusses the impact on real estate prices in East China and the classification of high-income and low-income regions based on GDP per capita. The fourth part is the empirical part of the paper. Through experiments, the factors affecting real estate prices in high-income and lowincome areas are studied. Through the research results, it is found that the CPI index is the most critical factor affecting real estate prices, and per capita urban area is the least important factor affecting real estate prices. In high-income and low-income city groups, except the CPI index, the extent to which per capita income, per capita urban area and per capita loans affect real estate prices is heterogeneous. The last section summarizes the research findings and the limits of this thesis.
Vedoucí práce: Georgi Burlakov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses